Biomass, Biofuels, Biochemicals : Circular Bioeconomy: Technologies for Biofuels and Biochemicals - Varjani, Sunita [Ed.]; Pandey, Ashok [Ed.]; Bhaskar, Thallada [Ed.]; Mohan, S. Venkata [Ed.]; Tsang, Daniel C.W. [Ed.] (Cambridge : Elsevier, 2022)
Biomass, Biofuels, Biochemicals: Circular Bioeconomy: Technologies for Biofuels and Biochemicals provides comprehensive information on strategies and approaches that facilitate the integration of technologies for the production of bio-based fuels, chemicals and other value-added products from wastes with waste biorefinery concepts and green strategies. The book also covers lifecycle assessment and techno-economic analyses of integrated biorefineries within a circular bioeconomy framework. As there has been continual research on new designs in production and consumerist approaches as we move towards sustainable development by scientists of various disciplines, law makers, environmental activists and industrialists, this book provides the latest details. Resources consumption and environment degradation necessitates a transition of our linear economy towards sustainable social and technical systems. As fossil resources are only projected to fulfill the needs of the population for the next couple of centuries, new tactics and standards must be created to ensure future success.
Keywords: Technology; Chemical engineering; Technology of explosives, fuels, related products; Artificial fuel